Socio-economic, Political, Legal and Financial Parameters of Civil Society - Anastasiya S. Tumanova; Aleksander A. Safonov (Финансы: теория и практика, 2017)
Topic. The article examines the socio-economic and political-legal characteristics of civil society formulated by leading Western scholars and approbated in the course of civil self-organization in Eastern Europe. We analyse recent Western theories of civil society that are relevant in describing processes in the modern Russian society, developing in a dynamic relationship between tolerance and paternalism overcoming the deficit of democracy and people’s participation.Purpose. The purpose of this study was the analysis of the relevant normative theories of civil society that sets the socio-economic and political context of the processes of self-organization in the modern world.Methodology and results. The authors formulate the concept of civil society based on the clarification of its content, key actors and their mutual relationships; discuss the role of the welfare state and social capital in the system of factors of development of civil society; find out the specifics of the functioning of civil society in the Russian Federation.Significant attention is paid to the rationale for such institutions of civil society as market economy, rights and freedoms of the citizen. They are defined as setting the outer frame of the development of civil society, because namely functioning institutions and their harmonious interaction ensure the development of civil self-organization.The market is treated as forming factor of institutional conditions for the development of civil society in the postSoviet space. The article offers possible directions for further improvement of civil society institutions in their interconnection and interaction. A prominent place is given to the financial situation of non-profit organizations (NPOs) as a key institution of civil society, the specificity of formation of their income, grant support for NGOs from the Russian Federation and the legislation on socially oriented NGOs.Conclusion. We conclude that there are the positive trends in the field of financing NGOs from the state; selective expert grant support of effective NGOs in 2017 is interpreted as a factor of stabilization of socio-political life in Russia.